Social Media Utilisation and its Implications for Student Ethics in Higher Education - Deviv, Selvia; Asri; Lawa, Farida Rurung (Cendekiawan Indonesia Timur, 2024)
Social media has become an integral part of the educational life of higher education students in Indonesia. Its use provides a variety of benefits, ranging from facilitating access to information, collaboration between students, to facilitating the exchange of ideas. However, in the perfection of its benefits, social media also poses serious challenges related to digital ethics, including the problem of cyberbullying, the spread of hoaxes, and privacy violations. Research on the impact of social media use shows a significant influence on learners' behaviour and achievement, both positive and negative. The importance of paying attention to how learners interact, manage content, and their adherence to digital ethics rules and norms is highlighted. Through an in-depth understanding of the usage patterns and impact of social media on students' ethics, this research aims to provide important insights for students, lecturers, and educational policy makers. It is hoped that the results of this research will not only provide a foundation for responsible policies on social media use in educational settings, but also trigger students' awareness of the impact of their online behaviour on the real world.